Hot Seat Strategy Improves Arabic Speaking Proficiency in Islamic Junior Secondary Classrooms: A Quasi-Experimental Study - Indah Fajriyati; Zaki Ghufron (Lingu, 2025)
Purpose – This study examined whether the Hot Seat strategy yields greater gains in Arabic speaking proficiency than conventional instruction among Grade 8 learners. Design/methods/approach – A quasi-experimental pretest–posttest design with intact classes was implemented at Islamic Junior High School (MTs) Fathur Rabbani, Cisoka–Tangerang, with 44 students allocated to an experimental class (Hot Seat) and a control class (conventional lessons). Speaking performance was assessed individually using parallel tasks at baseline and post-intervention, and group means and gains were compared. Findings – The experimental class improved from 48.64 to 81.36 (mean gain = 32.73), while the control class rose from 55.00 to 68.64 (mean gain = 13.64), producing a between-group gain difference of 19.09 points in favor of Hot Seat. These results indicate that structured role rotation, calibrated questioning, and rapid formative feedback can substantially increase both the quantity and quality of meaningful oral turns within equivalent instructional time. Research implications – The findings support the pedagogical value of dialogic, accountability-rich routines for accelerating Arabic speaking proficiency in junior secondary settings. Limitations include intact-class allocation without randomization, a single-site context, a relatively short intervention window, and the absence of a delayed posttest to assess retention. Future research should employ multi-site cluster-randomized trials with preregistered analyses, include delayed and transfer posttests, compare teacher-led versus student-led questioning formats, measure mediators such as engagement and state anxiety, and examine fidelity, equity, and cost-effectiveness. Overall, the study provides classroom-ready evidence that Hot Seat is an efficient, scalable approach to improving oral proficiency in Arabic.